PENGARUH PERBANDINGAN TANAH DAN KOMPOS DAUN LAMTORO (Leucaena leucocephala) TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA FASE MAIN NURSERY - Yusnaweti, Yusnaweti; Yulfidesi, Yulfidesi; Jamilah, Jamilah; Suryani, Suryani; Minhaminda, Minhaminda; Madani, Rona Tri (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
SOIL-Leucaena leucocephala LEAF COMPOST MIXTURE AS AMENDMENT IN POLYBAG-GROWING MEDIA FOR IMPROVEMENT OIL PALM SEEDLINGS AT MAIN NURSERY STAGE]. Production of oil palm seedling in the nursery mainly utilises top soil as polybag medium. These soils have low fertility especially N and organic matter content. The aim of this study was to determine the effects of top soil and leaf compost incorporation as amendment in polybag medium for oil palm seedlings growth at the nursery stage. This research was carried out at the Paranet House Experimental Garden and Laboratory of the Faculty of Animal Husbandry, Muhammadiyah University, West Sumatra from March to July 2022 using a standard period for oil palm seedling production in main nursery stage with five soil-leaf compost mixture (control, 1: 1, 1: 2, 1: 3, and 1: 4 v/v) as treatments. The treatments were arranged in a Completely Randomized Design (CRD) with three replications and each replication consisted of four polybags. The results showed that soil-leaf compost mixture (1: 4) was the best ratio for the growth of oil palm seedlings.